Perbandingan Berbagai Metode Pengecatan Spora pada Bacillus Cereus - Widodo, Widodo; Purlinda, Devi Etivia; Riadi, Ahmad (Poltekkes Kemenkes Semarang, 2022)
Endospores are formed by members of several genera of gram-positive bacteria, such as Bacillus and Clostridium. The spores are very resistant structurally; withstand the temperature of boiling water for two hours or more. They contain very little water and show very few chemical reactions. The favorable external environment will cause the spores to break down and the vegetative cells to appear to grow and reproduce. Identification of endospore-forming pathogens is important in food and medical microbiology. However, the spores contain multiple protective layers, which cannot be easily penetrated by simple staining or Gram staining techniques. Therefore, it is necessary to apply heat to help penetrate the color, with various methods of Gram stain, fluorescent spore painting, Schaeffer and Fulton spore painting and Client's spore painting method. The results of the fluorescent painting method have better results but require much more expensive equipment using a fluorescent microscope considering the facilities that must be provided for the Schaeffer and Fulton painting method as an alternative if they do not have these facilities.